Pseudomonas aeruginosa (IntechOpen, 2023)
Emerging antibiotic resistance of bacteria is driving us to catastrophic failure of the healthcare system. Pseudomonas aeruginosa is one such pathogen that is responsible for causing nosocomial infections, urinary tract infections, cystic fibrosis, otitis media, and infections of wounds and burns. P. aeruginosa is a critical pathogen as defined by the World Health Organization (WHO) due to its intrinsic and adaptive competence to defy antibiotics and persist as a superbug. This book covers a wide array of subjects relevant to bacterial biofilms specifically focusing on P. aeruginosa and associated infections. It provides readers with a clear and comprehensive overview of biofilm formation and associated detrimental impacts. In addition, this book also examines topics related to biosynthesis virulence factors by P. aeruginosa to facilitate biofilm formation, antibiotic resistance mechanisms, and infections.